Development of a New Deodorization Method of Herring Milt Hydrolysate: Impacts of pH, Stirring with Nitrogen and Deaerator Treatment on the Odorous Content - Sarah Todeschini; Véronique Perreault; Charles Goulet; Mélanie Bouchard; Pascal Dubé; Yvan Boutin; Laurent Bazinet (Foods, 2021)
Herring milt hydrolysate (HMH) presents the disadvantage of being associated with an unpleasant smell limiting its use. Thus, to develop a new effective and easy-to-use deodorization method, this research aimed to deepen the knowledge regarding the impacts of pH (pH 7 vs. pH 10), overnight stirring with nitrogen (+N vs. −N) and deaerator treatment (+D vs. −D) on the odorous content of HMH. This latter included dimethylamine (DMA), trimethylamine (TMA), trimethylamine oxide (TMAO) and the most potent odor-active compounds of HMH. Results showed that pH had a huge impact on the targeted compounds resulting in higher detected concentrations of DMA, TMA and TMAO at pH 10 than at pH 7 (p < 0.05) while the opposite trend was observed for the most potent odor-active compounds of HMH (p < 0.05). Moreover, independently of the pH condition, the overnight stirring with or without nitrogen had no impact (p > 0.05). Finally, the deaerator treatment was more effective to remove TMA and DMA at pH 10 than at pH 7 (p < 0.05) while the opposite trend was observed for the most potent odor-active compounds (p < 0.05). Sensory analysis confirmed that the application of pH 10 −N +D and pH 7 −N +D + alkalization pH 10 conditions led to the least odorous products (p < 0.05).